2005
DOI: 10.1289/ehp.7685
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones in Pregnancy in Relation to Environmental Exposure to Organochlorine Compounds and Mercury

Abstract: Polychlorinated biphenyls (PCBs), chlorinated pesticides, and mercury are global environmental contaminants that can disrupt the endocrine system in animals and humans. However, there is little evidence that they can interfere with endocrine status in pregnant women and neonates at low levels of exposure. The aim of this study was to examine thyroid hormone levels during pregnancy and in cord blood in relation to blood concentrations of organochlorine compounds (OCs) and Hg in healthy women recruited during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
5
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 67 publications
9
122
5
12
Order By: Relevance
“…Consistent with our results was a recent Canadian study of 149 pregnant women found a significant inverse relationship between low, environmental levels of HCB, PCB 153 and ΣPCBs in plasma and total T 3 , but no associations with free T 4 and TSH (Takser et al 2005). Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our results was a recent Canadian study of 149 pregnant women found a significant inverse relationship between low, environmental levels of HCB, PCB 153 and ΣPCBs in plasma and total T 3 , but no associations with free T 4 and TSH (Takser et al 2005). Likewise, inverse associations between PCBs and T 3 levels were also previously observed in the wives of Swedish fishermen (Hagmar et al 2001b) and in German schoolchildren (Osius et al 1999), while another study among Dutch women reported an inverse association with T 3 that was also accompanied by an inverse association with T 4 and a positive association with TSH (Sala et al 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Inconsistent with our findings were results from two other human studies that found no associations between p,p′-DDE and thyroid hormones in adult men (Hagmar et al 2001a;Persky et al 2001). Also inconsistent with our results but consistent with what they reported for HCB and PCBs, Takser et al (2005) found an inverse association between p,p′-DDE and total T 3 with no associations between p,p′-DDE and free T 4 or TSH in pregnant women. Based on the limited amount of available human data, the association between p,p′-DDE and thyroid hormones needs to be explored in other epidemiologic studies to support or refute our findings.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…For all studies, PCB levels (median or mean) are reexpressed in terms of μg/l serum, by the methods of Longnecker (Longnecker, 2001). Except for the study from Germany (Osius et al, 1999) of school children exposed to a toxic waste incineration plant, all other studies are from cohorts of infants or mothers with no particular exposures, from Holland (Koopman-Esseboom et al, 1994;Fiolet et al, 1997), North Carolina (Longnecker et al, 2000;Rogan et al, 1986), Taiwan , and Québec (Canada) (Takser et al, 2005). The combination of the highest exposures and the second largest sample size makes the Faroe Islands study the most useful.…”
Section: Pcbs Hypotonia and Thyroid Functionmentioning
confidence: 99%